Sequential determination of lead and cobalt in tap water and foods samples by fluorescence - Talio, María Carolina (2014)
In this work, a new procedure was developed for the separation and preconcentration of lead(II) and cobalt(II) in several water and foods samples. Complexes of metal ions with 8-hydroxyquinolein (8-HQ) were formed in aqueous solution. The proposed methodology is based on the preconcentration/separation of Pb(II) by solid-phase extraction using paper filter, followed by spectrofluorimetric determination of both metals, on the solid support and the filtered aqueous solution, respectively. The solid surfase fluorescence determination was carried out at λem = 455 nm (λex = 385 nm) for Pb(II)-8-HQ complex and the fluorescence of Co(II)-8-HQ was determined in aqueous solution using λem = 355 nm (λex = 225 nm). The calibration graphs are linears in the range 0.14 to 8.03 104 μg L−1 and 7.3× 10−2 to 4.12 × 103 μg L−1, for Pb(II) and Co(II), respectively, with a detection limit of 4.3 10−2 and 2.19 10−2 μg L−1 (S/N = 3). The developed methodology showed good sensitivity and adequate selectivity and it was successfully applied to the determination of trace amounts of lead and cobalt in tap waters belonging of different regions of Argentina and foods samples (milk powder, express coffee, cocoa powder) with satisfactory results. The new methodology was validated by electrothermal atomic absorption spectroscopy with adequate agreement. The proposed methodology represents a novel application of fluorescence to Pb(II) and Co(II) quantification with sensitivity and accuracy similar to atomic spectroscopies.